2018
DOI: 10.1074/jbc.ra118.004838
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity in oligomerization, operator architecture, and DNA binding in the mode of action of a bacterial B12-based photoreceptor

Abstract: Edited by Ruma Banerjee Newly discovered bacterial photoreceptors called CarH sense light by using 5-deoxyadenosylcobalamin (AdoCbl). They repress their own expression and that of genes for carotenoid synthesis by binding in the dark to operator DNA as AdoCblbound tetramers, whose light-induced disassembly relieves repression. High-resolution structures of Thermus thermophilus CarH Tt have provided snapshots of the dark and light states and have revealed a unique DNA-binding mode whereby only three of four DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 53 publications
1
27
0
Order By: Relevance
“…In non-phototrophic bacteria, the control of carotenoid production is classified into three types: constitutive, light-inducible, and cryptic manner 7 . We and other groups have been studying the phenomena and molecular mechanism of light-inducible production of carotenoids of phylogenetically different bacteria including S. coelicolor A3(2) 8 , Thermus thermophilus HB27 914 , Bacillus megaterium QM B1551 15,16 , Mycobacterium marinum 17 , and Arthrobacter arilaitensis 18 . Our study has revealed that LitR/CarH family proteins, a MerR family transcriptional regulator retained by S .…”
Section: Introductionmentioning
confidence: 99%
“…In non-phototrophic bacteria, the control of carotenoid production is classified into three types: constitutive, light-inducible, and cryptic manner 7 . We and other groups have been studying the phenomena and molecular mechanism of light-inducible production of carotenoids of phylogenetically different bacteria including S. coelicolor A3(2) 8 , Thermus thermophilus HB27 914 , Bacillus megaterium QM B1551 15,16 , Mycobacterium marinum 17 , and Arthrobacter arilaitensis 18 . Our study has revealed that LitR/CarH family proteins, a MerR family transcriptional regulator retained by S .…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, apo-CarH from Bacillus megaterium has also been shown to self-interact independently of AdoCbl, but to a signicantly greater extent than for TtCarH. 9 apo-BmCarH elutes in SEC as a molten globule (i.e., loosely packed) oligomeric species with a molecular weight consistent with a trimer, although these oligomeric states do not bind DNA. AdoCbl-binding to BmCarH induces tetramer formation, which is much more rigidly structured (and binds DNA in vivo) and dissociates into dimers instead of monomers upon illumination.…”
Section: Discussionmentioning
confidence: 99%
“…7 AdoCbl photochemistry in CarH results in transcriptional activation in bacteria, which leads to the biosynthesis of carotenoids in response to photo-oxidative stress. Mechanistic details about its function are now beginning to emerge 4,[6][7][8][9][10][11] and it is already showing great promise and versatility as the basis of photoactivated, biomolecular tools. [12][13][14][15][16] The size and structural complexity of AdoCbl reect a long and expensive biosynthetic pathway 17 and mean that its uptake 18 and subsequent binding to its dependent enzymes 19 are oen tightly regulated.…”
Section: Introductionmentioning
confidence: 99%
“…Both homologs turned out to be B 12 -dependent like CarH. Studies of the homolog in the Gram-negative Thermus thermophilus , CarH Tt , yielded valuable biochemical [ 20 ], structural [ 19 ] and photochemical insights [ 61 , 62 , 63 ] that were further extended with CarH Bm , the homolog in the Gram-positive Bacillus megaterium [ 64 , 65 ]. These findings, reviewed elsewhere [ 21 , 22 ], are briefly highlighted here.…”
Section: Direct Light Sensing Signal Transduction and Gene Regulation By The B 12 -Based Carh Photoreceptormentioning
confidence: 99%
“…Studies of CarH Tt and CarH Bm revealed that light-dependent regulation of transcription relies on modulation of their oligomeric state by AdoCbl and light ( Figure 2 c) [ 19 , 20 , 21 , 22 , 64 , 65 , 66 ]. AdoCbl-free apoCarH Tt is a monomer and apoCarH Bm is a loosely folded molten globule tetramer, and both bind poorly to operator DNA.…”
Section: Direct Light Sensing Signal Transduction and Gene Regulation By The B 12 -Based Carh Photoreceptormentioning
confidence: 99%